2017
DOI: 10.3390/ijms18102131
|View full text |Cite
|
Sign up to set email alerts
|

Association between Stress and the HPA Axis in the Atopic Dermatitis

Abstract: The hypothalamic–pituitary–adrenal (HPA) axis is one of the body’s neuroendocrine networks that responds to psychological stress (PS). In the skin, there exists a peripheral HPA axis similar to the central axis. Glucocorticoids (GCs) are key effector molecules of the HPA axis and are essential for cutaneous homeostasis. Atopic dermatitis (AD) is a condition typically characterized by a chronic relapsing course that often results in PS. HPA dysfunction is present in AD patients by the decreased response of GCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 124 publications
(199 reference statements)
1
86
0
6
Order By: Relevance
“…Recently, a hypothesis of the gut-brain-skin axis is being developed [68]. It has been proved that various skin disorders (urticarial, atopic dermatitis, psoriasis) have a strong correlation with the emotional status of the patient [69,70,71,72]. It has been shown that there is a negative influence on the immune system causing a greater risk of infections in patients subjected to mild to severe chronic stress [72].…”
Section: State Of Knowledgementioning
confidence: 99%
“…Recently, a hypothesis of the gut-brain-skin axis is being developed [68]. It has been proved that various skin disorders (urticarial, atopic dermatitis, psoriasis) have a strong correlation with the emotional status of the patient [69,70,71,72]. It has been shown that there is a negative influence on the immune system causing a greater risk of infections in patients subjected to mild to severe chronic stress [72].…”
Section: State Of Knowledgementioning
confidence: 99%
“…The associations between stress and itch in patients with AD constitute a problem of particular complexity and importance and involve the components of the so-called neuro-endocrino-immunocutaneous system (NEICS) and the hypothalamo-pituitary-adrenal (HPA axis). The relevant aspects of this issue are covered in detail elsewhere (33)(34)(35)(36)(37)(38), although there is evidence that acute or chronic stress have different impacts on the HPA axis (39).…”
Section: Itch and Stressmentioning
confidence: 99%
“…Olive oil contains linoleic acid, which is defined as an essential fatty acid for humans that is beneficial for skin health by overcoming problems related to scaly skin, eczema, and dry skin. Olive oil helps with pressure problems associated with thrombotic and vasoconstriction issues, especially in the peripheral circulation system (Lin, Zhong, & Santiago, 2017). Olive oil has a hard nature to remove the remains of dead skin but is soft for the skin.…”
Section: Discussionmentioning
confidence: 99%